2023
DOI: 10.3390/ani13223581
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of a Transposable Element Expression Atlas during 27 Developmental Stages in Porcine Skeletal Muscle: Unveiling Molecular Insights into Pork Production Traits

Chao Wang,
Bowen Lei,
Yuwen Liu

Abstract: The development and growth of porcine skeletal muscle determine pork quality and yield. While genetic regulation of porcine skeletal muscle development has been extensively studied using various omics data, the role of transposable elements (TEs) in this context has been less explored. To bridge this gap, we constructed a comprehensive atlas of TE expression throughout the developmental stages of porcine skeletal muscle. This was achieved by integrating porcine TE genomic coordinates with whole-transcriptome R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
0
0
Order By: Relevance
“…The gene expression level of ACTC1 , a cardiac muscle protein that pivotal in cellular division, migration, and vesicular transport [ 77 ], was significantly higher at D21 than at D42 in broiler chickens. ACTC1 has been identified in both bovine and porcine skeletal muscle tissue and muscle cells [ 78 , 79 ], signifying its enrichment in the pathway related to muscle contraction. In addition, studies have shown that ACTC1 plays a crucial supportive role in the maintenance of human Pax7 + myogenic progenitor cells and the promotion of muscle regeneration after injury [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…The gene expression level of ACTC1 , a cardiac muscle protein that pivotal in cellular division, migration, and vesicular transport [ 77 ], was significantly higher at D21 than at D42 in broiler chickens. ACTC1 has been identified in both bovine and porcine skeletal muscle tissue and muscle cells [ 78 , 79 ], signifying its enrichment in the pathway related to muscle contraction. In addition, studies have shown that ACTC1 plays a crucial supportive role in the maintenance of human Pax7 + myogenic progenitor cells and the promotion of muscle regeneration after injury [ 80 ].…”
Section: Discussionmentioning
confidence: 99%